2020
DOI: 10.1177/0846537120914247
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Comprehensive Imaging of the Major Trauma Patient: A New Paradigm for Improved Clinical Decision-Making

Abstract: Modern advances in the medical imaging layered onto sophisticated trauma resuscitation strategies in highly organized regionalized trauma systems have created a paradigm shift in the management of severely injured patients. Although immediate exploratory surgery to identify and control life-threatening injuries still has its place, accelerated image acquisition and interpretation procedures now make it rare for trauma surgeons in major centers to venture into damage control surgery unaided by computed tomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…In-house imaging would prevent these scenarios. Exclusive access to imaging and radiology teams would also allow for bedside imaging, so that patients would not leave the unit or nurses’ observation, a critical factor during MCIs, as patients in this case may be highly unstable and so require continuous supervision (Qamar et al, 2020). Gil et al (2020) found that locating a dedicated MRI scanner in ED enables faster hip fracture diagnosis and surgical consultation without also increasing ED throughput time.…”
Section: Discussionmentioning
confidence: 99%
“…In-house imaging would prevent these scenarios. Exclusive access to imaging and radiology teams would also allow for bedside imaging, so that patients would not leave the unit or nurses’ observation, a critical factor during MCIs, as patients in this case may be highly unstable and so require continuous supervision (Qamar et al, 2020). Gil et al (2020) found that locating a dedicated MRI scanner in ED enables faster hip fracture diagnosis and surgical consultation without also increasing ED throughput time.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some authors in their well written review pointed out that diagnosing occult injuries with routine WBCT allows of safe and fast disposition from ED and obviates requiring of subsequent imaging and medical evaluation when patients present for follow-up with nonspecific pain or other complaints. [18] And, rightly again, they concluded that even some minor injuries, that may be misdiagnosed when WBCT wasn't used, can be fatal in the special population.…”
Section: Discussionmentioning
confidence: 99%
“…Bedside imaging has an important role in the urgent management of patients with severe trauma. Chest radiography in patients with respiratory distress and pelvic radiography in patients with suspected pelvic fractures assist in initiating rapid stabilization procedures prior to computed tomography (CT) [ 16 ]. However, routine radiography and focused abdominal sonography in trauma (FAST) in stable patients should not delay transfer once a decision to perform CT has been made [ 17 ].…”
Section: Radiology Decision-makingmentioning
confidence: 99%